Leguminosas arbustivas en sistemas de producción en el trópico - Kerridge, Peter C.; Lascano Aguilar, Carlos Eduardo (International Center for Tropical Agriculture, 1996)
Special characteristics of shrub legumes that make their use attractive in tropical production systems are briefly presented, as well as several constraints. Examples are then given of their use in diverse production systems. These species, once established, can become a permanent component of the farming system. This characteristic of longevity is often related to slow establishment and, accordingly, to a long period before the shrubs can be fully utilized. This is valid for shrub species grown either for feed animals or for other uses. These species, however, are frequently used as pioneers to recover degraded areas. Just like herbaceous legumes, they are capable of fixing atmospheric N so it can later be used by associated species. Most shrub legumes are highly tolerant of drought and are capable of surviving in these conditions; for example, Cratylia argentea maintains green leaves during the dry season. One of the constraints to using these plants in production systems is their slow establishment. For some species, another key constraint is the low nutritive value due to the presence of antiquality factors.